Attrition when providing antiretroviral treatment at CD4 counts >500cells/mu L at three government clinics included in the HPTN 071 (PopART) trial in South Africa - Bock,P; Fatti,G; Ford,N; Jennings,K; Kruger,J; Gunst,C; Louis,F; Grobbelaar,N; Shanaube,K; Floyd,S; Grimwood,A; Hayes,R; et al. (PLoS ONE, 2018)
Introduction: WHO recommends antiretroviral treatment (ART) for all HIV-positive individuals. This study evaluated the association between baseline CD4 count and attrition in a cohort of HIV positive adults initiating ART at three department of health (DOH) clinics routinely providing ART at baseline CD4 counts >500cells/μL for the HPTN 071 (PopART) trial.Methods:All clients attending the DOH clinics were managed according to standard care guidelines with the exception that those starting ART outside of pertinent local guidelines signed research informed consent. DOH data on all HIV-positive adult clients recorded as having initiated ART between January 2014 and November 2015 at the three study clinics was analysed. Attrition, included clients lost to follow up or died, and was defined as ‘being three or more months late for an antiretroviral pharmacy pick-up appointment’. All clients were followed until attrition, transfer out or end May 2016.Results:A total of 2423 clients with a median baseline CD4 count of 328 cells/μL (IQR 195–468) were included of whom 631 (26.0%) experienced attrition and 140 (5.8%) were TFO. Attrition was highest during the first six months of ART (IR 38.3/100 PY; 95% CI 34.8–42.1). Higher attrition was found amongst those with baseline CD4 counts > 500 cells/μL compared to those with baseline CD4 counts of 0–500 cells/μL (aHR 1.26, 95%CI 1.05 to 1.52) This finding was confirmed on subset analyses when restricted to individuals non-pregnant at baseline and when restricted to individuals with follow up of > 12months.Conclusions:Attrition in this study was high, particularly during the first six months of treatment. Attrition was highest amongst clients starting ART at baseline CD4 counts > 500 cells/μL. Strategies to improve retention amongst ART clients, particularly those starting ART at baseline CD4 counts >500cells/μL, need strengthening. Improved monitoring of clients moving